Peculiarities of Legislative Interactions with Public Policy in Lithuania - Urmonas, Algimantas (Viešoji politika ir administravimas, 2019)
Legislative public policy in Lithuania is a specific area of state activity, where the reasons for the purpose of lawmaking and change are analyzed. Also decisions are made to improve the drafting of laws and the accompanying legislation, to increase the efficiency of legal regulation, and the legislative measures try to solve social problems. However, the formation of legislative provisions in the field of public policy and administration of its implementation in Lithuania is characterized not only by links, but also by large gaps between these phenomena, because of the linkup and confrontation between different interests. And this is perfectly understandable, because public policy is based on a utility and law is a paradigm of justice. That is why politicians use the legislative powers in the context of todayʼs reality, having a multiplicity of interests, not only duplicates by his behaviour, but sometimes also focuses on a larger scale of social roles. A politician, who at the same time is a legislative subject, focuses not only on the electorate, but also on the political interests of the political party, and the protected economic interests of business representatives. Finally, he has some personal interests in his presence in power. As the dysfunctional legislative practice shows, there are also cases where the main goal of the politician is not justice, but the desire to gain as much populist popularity as possible, in the hope that all the ways are good: disregard for laws, nihilistic thinking that eliminates the sense of reality and delete the boundaries of differences between illusion and reality. DOI: http://dx.doi.org/10.5755/j01.ppaa.18.1.23131